The Development of Bio-Industrial Agricultural Model on Dry Land - I Ketut Arnawa; Menardo Dennis Villanueva; Ni Gusti Agung Gde Eka Martiningsih; Putu Sri Astuti; Putu Eka Pasmidi Ariati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Bio-industrial agriculture is a farming system oriented towards biological and natural resources maximum utilization as sustainable biomass, energy, and mineral. Vegetable and horticulture-based bio-industrial agriculture is a sustainable system consisted of farming, livestock, sewage treatment, agricultural product processing, and marketing sub-systems. The main objective of this study was to analyze the impact of the bio-industrial agricultural model development on the value-added agriculture. This study was conducted on dry land in Antapan Village, Baturiti District, Tabanan, Bali. Questionnaires and interview sessions were applied to collect the study data. Data analysis was done by descriptive analysis, a ratio of R/C, and multiple linear regression analysis. Findings revealed that bio-industrial agriculture contibuted to higher value-added agriculture. Vegetable and horticulture-based bio-industrial agriculture provided alternative system for the development of processed organic agricultural products that finally adds more product's value and increase farmer income.